The blood copper isotopic composition is a prognostic indicator of the hepatic injury in Wilson disease. Issue 11 (15th October 2020) - Lamboux, Aline; Couchonnal-Bedoya, Eduardo; Guillaud, Olivier; Laurencin, Chloé; Lion-François, Laurence; Belmalih, Abdelouahed; Mintz, Elisabeth; Brun, Virginie; Bost, Muriel; Lachaux, Alain; Balter, Vincent
Abstract : The blood copper isotope composition recapitulates Wilson Disease progression and is therefore a potential prognostic biomarker. Abstract : Wilson disease (WD) is an autosomal recessive disorder of copper (Cu) metabolism. The gene responsible for WD, ATP7B, is involved in the cellular transport of Cu, and mutations in the ATP7B gene induce accumulation of Cu in the liver and ultimately in the brain. In a pilot study, the natural variations of copper stable isotope ratios ( 65 Cu/ 63 Cu) in the serum of WD patients have been shown to differ from that of healthy controls. In the present study, we challenged these first results by measuring the 65 Cu/ 63 Cu ratios in the blood of treated ( n = 25), naïve patients ( n = 11) and age matched healthy controls ( n = 75). The results show that naïve patients and healthy controls exhibit undistinguishable 65 Cu/ 63 Cu ratios, implying that the Cu isotopic ratio cannot serve as a reliable diagnostic biomarker. The type of treatment (d -penicillamine vs. triethylenetetramine) does not affect the 65 Cu/ 63 Cu ratios in WD patients, which remain constant regardless of the type and duration of the treatment. In addition, the 65 Cu/ 63 Cu ratios do not vary in naïve patients after the onset of the treatment. However, the 65 Cu/ 63 Cu ratios decrease with the degree of liver fibrosis and the gradient of the phenotypic presentation, i.e. presymptomatic, hepatic and neurologic. To get insights into the mechanisms at work, we study the effects of the progress of the WD on the organism by measuring the Cu concentrations and the 65 Cu/ 63 Cu ratios in the liver, feces and plasma of 12 and 45 week old Atp7b −/− mice. The evolution of the 65 Cu/ 63 Cu ratios is marked by a decrease in all tissues. The results show that 63 Cu accumulates in the liver preferentially to 65 Cu due to the preferential cellular entry of 63 Cu and the impairment of the 63 Cu exit by ceruloplasmin. The hepatic accumulation of monovalent 63 Cu + is likely to fuel the production of free radicals, which is potentially an explanation of the pathogenicity of WD. Altogether, the results suggest that the blood 65 Cu/ 63 Cu ratio recapitulates WD progression and is a potential prognostic biomarker of WD.